Frequency of Fetal Hemoglobin Level in Siblings of Betathalassemia Major patients - Nasir Rashid, Almas Raza, Syed Zeeshan Haider Naqvi, Sheema Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To see the frequency of fetal haemoglobin level in siblings of beta thalassemia major (BTM) patients. Study population: A total of 400 subjects were included. Grouping: Group A includes normal siblings of BTM cases, B includes beta thalassemia trait (BTT) siblings of BTM cases and group C were healthy controls. Selection criteria: Asymptomatic siblings of diagnosed cases of beta thalassemia major were included. Patients with history or diagnosis of any acute or chronic illnesses were excluded from the study. 5 ml of blood was taken in EDTA vial and used for haemoglobin electrophoresis. Results: In 200 cases, 78% (156) were beta thalassemia trait (BTT) siblings and fetal Hb was also more in BTT siblings i.e. Group B. Conclusion: Fetal haemoglobin (HbF) was increased in BTT siblings (group B) of BTM cases. Keywords: Hb electrophoresis, fetal Hb, beta thalassemia major